Oxidative Stress Is a Key Modulator in the Development of Nonalcoholic Fatty Liver Disease - Yuanqiang Ma; Gyurim Lee; Su-Young Heo; Yoon-Seok Roh (MDPI AG, 2021)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide, and scientific studies consistently report that NAFLD development can be accelerated by oxidative stress. Oxidative stress can induce the progression of NAFLD to NASH by stimulating Kupffer cells, hepatic stellate cells, and hepatocytes. Therefore, studies are underway to identify the role of antioxidants in the treatment of NAFLD. In this review, we have summarized the origins of reactive oxygen species (ROS) in cells, the relationship between ROS and NAFLD, and have discussed the use of antioxidants as therapeutic agents for NAFLD.